Making history matter more in evolutionary economic geography - Ron Martin; Peter Sunley (ZFW - Advances in Economic Geography, 2022)
Our focus in this paper is on a somewhat curious feature of evolutionary economic geography, namely that although concerned with evolution - with processes of historical change and transformation - evolutionary economic geography seems not to take history as seriously as it would be expected to do. We argue that evolutionary economic geography is inescapably an historical social science, and that as such would benefit from exploring the different ways in which history can be used in causal investigation, from problematising the different temporalities of economic change and transformation, and from giving more attention to appreciative theorising and narrative case study over variable-centred approaches.
Keywords: R11; R12; B52; 330; Appreciative theorising; Evolutionary economic geography; Historical cognizance; History; History-in-theory; History-to-theory; Narrative methods; Temporalities